The Influence of Leadership Style and Organizational Culture on Employee Performance - Budi Cahyono, Afrid; Wening, Nur (Riviera Publishing, 2023)
Human resources have an important role as implementers of company policies and operations so that they become the most important asset for an organization or company. To achieve the vision and mission of an organization or company's goals, leadership style and organizational culture play an important role in its success. This study aims to determine the effect of leadership style and organizational culture on employee performance. This literature study with secondary data is used as a research method. Data related to the research topic was obtained from national journal publications from 2017 to 2023. The results of the literature review analysis show that leadership style and organizational culture have a positive and significant effect on employee performance. This research implies that organizations can focus more on developing effective leadership styles, such as transformational or democratic, which have been shown to have a positive impact on employee performance. And building a supportive, inclusive, and motivating culture will be key in improving employee performance.